Antidepressant use during pregnancy and psychiatric disorders in offspring: Danish nationwide register based cohort study. (6th September 2017) - Liu, Xiaoqin; Agerbo, Esben; Ingstrup, Katja G; Musliner, Katherine; Meltzer-Brody, Samantha; Bergink, Veerle; Munk-Olsen, Trine
Abstract : Objective  To investigate the association between in utero exposure to antidepressants and risk of psychiatric disorders. Design  Population based cohort study. Setting  Danish national registers. Participants  905 383 liveborn singletons born during 1998-2012 in Denmark and followed from birth until July 2014, death, emigration, or date of first psychiatric diagnosis, whichever came first. The children were followed for a maximum of 16.5 years and contributed 8.1×10 6 person years at risk. Exposures for observational studies  Children were categorised into four groups according to maternal antidepressant use within two years before and during pregnancy: unexposed, antidepressant discontinuation (use before but not during pregnancy), antidepressant continuation (use both before and during pregnancy), and new user (use only during pregnancy). Main outcome measure  First psychiatric diagnosis in children, defined as first day of inpatient or outpatient treatment for psychiatric disorders. Hazard ratios of psychiatric disorders were estimated using Cox regression models. Results  Overall, psychiatric disorders were diagnosed in 32 400 children. The adjusted 15 year cumulative incidence of psychiatric disorders was 8.0% (95% confidence interval 7.9% to 8.2%) in the unexposed group, 11.5% (10.3% to 12.9%) in the antidepressant discontinuation group, 13.6% (11.3% to 16.3%) in the continuation group, and 14.5% (10.5% to 19.8%) in the new user group. The antidepressant continuation group had an increased risk of psychiatric disorders (hazard ratio 1.27, 1.17 to 1.38), compared with the discontinuation group. Conclusions  In utero exposure to antidepressants was associated with increased risk of psychiatric disorders. The association may be attributable to the severity of underlying maternal disorders in combination with antidepressant exposure in utero. The findings suggest that focusing solely on a single psychiatric disorder among offspring in studies of in utero antidepressant exposure may be too restrictive.